Assédio moral e outros danos na aposentadoria: conhecer, corrigir e superar - Fraiman, Ana Perwin (2010)
This thesis aims to reveal: the macro context, which is public and impersonal, and the micro level, which is private, highly personal and subjective, around time that has marked the withdrawal and retirement of those who are older from their jobs. The phenomena described here inscribe its history about what actually comprise and means retirement, in the midst of the current transformations in the labor market, at the same time it clarifies the subjective experiences lived by people close to retire. Presented within the transverse model of study and research, not only of related knowledge, interlacing the social sciences to other different areas, this thesis gathers a group of knowledge that, as a whole can better lead to understanding the paths taken to reach the precarious situation experienced by a large parcel of the population of all retired Brazilians and what other ways might be opened from that. This thesis focuses mainly on major areas of conflict and paradox, as well as search possibilities for dialogue between the old and new. Similarly, it demands to know how the human person has absorbed and metabolized the violence slaughtered on it by virtue of convulsive paradigmatic changes that occur. It refines its lenses, driving looks particularly to interpersonal relationships that are seen in the labor universe. It aims to inventory, interpret and narrate about the processes and mechanisms that people have adopted, and may also be able to use to create a new future: a future in where they have the freedom and autonomy to recreate and integrate the new reality that emerges. It is focusing on rituals that deny and others that dignify the value of the person, and seeks to understand what specifically happens in human relations within the organizational work space and within the institutions space that, often as a guillotine, prevent the person from continuing and use its vital forces, that allows it to signify their existential journey and recognize themselves in possession and enjoyment of full rights of citizenship